Australia : Staff Report for 2013 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for Australia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2013 Article IV consultation highlights Australia's below-trend GDP growth and the beginning of the decline of the investment phase of the mining boom, which has passed its peak. A key issue now is how Australia can manage the mining-production/export phase and encourage broader-based growth. The main external risks include a slowdown in China over the medium term and surges in global financial market volatility. The pickup in housing market activity, though welcome to date, could pose a future risk if prices accelerate and lead to overshooting. The financial sector is resilient and has strengthened in recent years, although banks' reliance on offshore funding will continue. The emphasis on tight lending standards and intensive supervision should help limit financial sector risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet